switchde: inference of switch-like differential expression along single-cell trajectories - Campbell, K; Yau, C (Oxford University Press, 2016)
MOTIVATION: Pseudotime analyses of single-cell RNA-seq data have become increasingly common. Typically, a latent trajectory corresponding to a biological process of interest - such as differentiation or cell cycle - is discovered. However, relatively little attention has been paid to modelling the differential expression of genes along such trajectories. RESULTS: We present switchde, a statistical framework and accompanying R package for identifying switch-like differential expression of genes along pseudotemporal trajectories. Our method includes fast model fitting that provides interpretable parameter estimates corresponding to how quickly a gene is up or down regulated as well as where in the trajectory such regulation occurs. It also reports a p-value in favour of rejecting a constant-expression model for switch-like differential expression and optionally models the zero-inflation prevalent in single-cell data. AVAILABILITY: The R package switchde is available at http://www.github.com/kieranrcampbell/switchde CONTACT: kieran.campbell@sjc.ox.ac.uk SUPPLEMENTARY INFORMATION: Supplementary text is available at Bioinformatics online.